2010
DOI: 10.19030/tlc.v7i2.89
|View full text |Cite
|
Sign up to set email alerts
|

Study Attitude And Academic Achievement At Secondary Level In Pakistan

Abstract: The author compared study attitudes of low and high achievers by using a self-developed study attitude scale (SAS) consisting of 36 items. Academic performance was measured through marks obtained by the students in the 9th grade examination conducted by the external body.  The analysis revealed that the study attitude of secondary school students was related with their academic achievement.  A t-test for independent samples showed that there was a significant difference between the study attitude of male, fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 4 publications
2
19
0
Order By: Relevance
“…Laxminarayanan et al (2006) and Sarwar et al (2009) found that overachievers possessed better study habits than underachievers while Sirohi (2004) concluded that poor study habits were one of the main causes for underachievement. Lidhoo and Khan (1990) observed that poor study habits and low need-achievement were associated with underachievement among bright subjects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Laxminarayanan et al (2006) and Sarwar et al (2009) found that overachievers possessed better study habits than underachievers while Sirohi (2004) concluded that poor study habits were one of the main causes for underachievement. Lidhoo and Khan (1990) observed that poor study habits and low need-achievement were associated with underachievement among bright subjects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This aspect was however not directly questioned in our survey. Sarwar et al 4 also demonstrated in their study that high achievers reported putting in more vigorous efforts; additionally, they said that they tried to understand things and not memorize them.…”
Section: Discussionmentioning
confidence: 86%
“…However, academic self-perceptions and motivation/selfregulation appeared to be stronger predictors of academic achievement status than attitude toward school and teachers. According to Sarwar et al, 4 high-achievers reported being more calm and efficient compared to low achievers. These students also found their school subjects relevant and interesting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations